ANALISIS PELAYANAN DI MAL PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT KABUPATEN SUMENEP - Elliyah El-Ghafur; Dina Kurniawati (Journal MISSY (Management and Business Strategy), 2020)
The purpose of this reserch is to find the service in public service mall to the satisfaction of the people of Sumenep regency. The research was qualitative descriptive study with observation, interview, and documentation data collection techniques. It used random sampling. The data were then analyzed with data collection, data reduction, data presentation, and withdrawal of conclusions. The results of this study showed that the public service mall of Sumenep district in providing service to the community has implemented five dimensions of service quality, which consists of: tangibel, realiability, responsiviness, assurance, and Emphaty. Based on the findings it can be concluded that service provided by the public service mall Sumenep district is already good, so that people who use the service is satisfied with the service they receive